2018
DOI: 10.1242/jcs.202002
|View full text |Cite
|
Sign up to set email alerts
|

miRNA targeting and alternative splicing in the stress response – events hosted by membrane-less compartments

Abstract: Stress can be temporary or chronic, and mild or acute. Depending on its extent and severity, cells either alter their metabolism, and adopt a new state, or die. Fluctuations in environmental conditions occur frequently, and such stress disturbs cellular homeostasis, but in general, stresses are reversible and last only a short time. There is increasing evidence that regulation of gene expression in response to temporal stress happens post-transcriptionally in specialized subcellular membrane-less compartments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 155 publications
(227 reference statements)
0
29
0
1
Order By: Relevance
“…A single miRNA could regulate many target genes at a time, and a single target mRNA could also be regulated by several miRNAs (Chowdhury et al, 2014;O'Brien et al, 2018), therefore implying the existence of the coordinated miRNA network in regulating the gene expression. Moreover, numerous evidence showing that the miRNA expression, regulatory action, and localization can change due to cellular environments (Ebert and Sharp, 2012;Kucherenko and Shcherbata, 2018). Serum starvation in multiple human cell lines has demonstrated that a significant decrease in intracellular miRNA levels with higher extracellular releases of these miRNAs either in vesicle form or as in circulating free miRNAs (Wang et al, 2010).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…A single miRNA could regulate many target genes at a time, and a single target mRNA could also be regulated by several miRNAs (Chowdhury et al, 2014;O'Brien et al, 2018), therefore implying the existence of the coordinated miRNA network in regulating the gene expression. Moreover, numerous evidence showing that the miRNA expression, regulatory action, and localization can change due to cellular environments (Ebert and Sharp, 2012;Kucherenko and Shcherbata, 2018). Serum starvation in multiple human cell lines has demonstrated that a significant decrease in intracellular miRNA levels with higher extracellular releases of these miRNAs either in vesicle form or as in circulating free miRNAs (Wang et al, 2010).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…MicroRNAs (miRNAs) have been reported to be implicated in many cell functions, such as proliferation, differentiation, development, and apoptosis . miRNAs are differentially expressed during the course of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…There are several possibilities. First, miRNA regulation and alternative splicing are two independent but closely related post‐transcriptional processes . miRNAs can directly target some alternative splicing factors, leading to changes in the alternative splicing profile.…”
Section: Discussionmentioning
confidence: 99%
“…First, miRNA regulation and alternative splicing are two independent but closely related post-transcriptional processes. 32 miRNAs can directly target some alternative splicing factors, leading to changes in the alternative splicing profile. It will be interesting to further investigate whether miR-378a-3p can alter the expression of the alternative splicing factors that can control splicing for specific MOR-1Bs.…”
Section: Discussionmentioning
confidence: 99%